2019
DOI: 10.30541/v58i2pp.159-176
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Agglomeration on Socio-economic Outcomes: A District Level Panel Study of Punjab

Abstract: This paper examines the variation of agglomeration across districts over time in Punjab and analyses the effects of agglomeration on socio-economic outcomes in terms of social inclusion and efficiency of firms at the district level in Punjab. Earlier studies in this regard faced multiple problems since they used cross-sectional data. To bridge the gap, a newly constructed panel data from CMI is used. Factor Analysis technique is used to analyse socialinclusion variable, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The demand for housing also has a significant positive relationship with education, in the long-run. Educated people move to cities for better living conditions (Azhar & Adil, 2016). Overall, the results show that AEs have a significant long-run impact on education index.…”
Section: Pooled Mean Group and Mean Group Estimatesmentioning
confidence: 76%
See 2 more Smart Citations
“…The demand for housing also has a significant positive relationship with education, in the long-run. Educated people move to cities for better living conditions (Azhar & Adil, 2016). Overall, the results show that AEs have a significant long-run impact on education index.…”
Section: Pooled Mean Group and Mean Group Estimatesmentioning
confidence: 76%
“…Agglomerations of localized and urbanized economies have a strong impact on formation of new firms, their scale of operation, employment, enrollment levels, and social-inclusion. However, this impact varies with firms' size (Azhar & Adil, 2016;Chaudhry & Haroon, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1970, a flux of labor migration toward the middle east countries (e.g., the United Arab Emirates and Saudi Arabia) (Azhar, 2008), and flood events in 1992, 1998, 2010(Ahmed et al, 2014Munir and Iqbal, 2016;Garcia et al, 2018) acted as trigger points that initiated urban migration from rural areas. Such migration, especially from the de-excluded areas, led the high land price and renters, unplanned construction activities, congested road development, improper green space management, and removal of agriculture and scrubland.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few countries analyzed in the context of this research is Pakistan, although the research is relatively scant: Burki and Khan (2010) also found that industrial concentration is a prominent characteristic of all districts of Punjab but is more apparent in the urbanized areas of the province. Azhar and Adil (2016) show that district‐level agglomeration is positively correlated with the efficiency of firms.…”
Section: Introductionmentioning
confidence: 99%